Lithium iron phosphate positive electrode material and preparation method and application thereof
By using iron-containing waste materials to prepare lithium iron phosphate positive electrode materials, the problems of uncontrollable iron phosphate ratio and high cost are solved, and high efficiency and low cost preparation of lithium iron phosphate positive electrode materials are achieved, with excellent electrochemical properties.
Patent Information
- Application Number
- CN202411483886.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-01-03
AI Technical Summary
In the preparation of lithium iron phosphate positive electrode material, the uncontrollable phosphorus-iron ratio leads to poor performance consistency, and the cost of iron phosphate is high, which limits the application range of lithium-ion batteries.
Iron-containing waste is used as the iron source, and lithium iron phosphate positive electrode material is prepared by acidification, filtration, adjustment of iron ion concentration, mixing precursors, spray-drying and sintering, which simplifies the process flow and reduces costs.
The preparation of high-purity lithium iron phosphate positive electrode material has been achieved, with excellent electrochemical performance, the first charge and discharge efficiency reaches 96.6%, and the raw material cost is reduced by about 15%, solving the problem of uncontrollable phosphorus-iron ratio.
Smart Images

Figure BDA0005098222880000051 
Figure BDA0005098222880000081 
Figure BDA0005098222880000091
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of cathode materials for batteries, and particularly relates to a lithium iron phosphate cathode material, a preparation method thereof, and an application thereof. Background Art
[0002] The lithium iron phosphate cathode material is a cathode active material in a lithium ion battery. It is mainly composed of lithium iron phosphate (LiFePO4). This compound has a stable olivine structure, providing good electrochemical performance for the battery. Due to its advantages such as high capacity (theoretical specific capacity of 170 mAh / g), high safety (non-toxic), long cycle life, environmental friendliness, and moderate energy density, it is one of the important cathode active materials in lithium ion batteries.
[0003] Currently, the lithium iron phosphate cathode material is mainly prepared from iron phosphate as a raw material. However, the phosphorus-iron ratio in iron phosphate is uncontrollable, resulting in poor performance consistency of lithium iron phosphate. At the same time, the cost of iron phosphate is relatively high, and the single-item cost reaches 50% of the raw material cost, which limits the cost of lithium ion batteries to a certain extent and thus restricts its application range. Summary of the Invention
[0004] The present invention provides a method for preparing a lithium iron phosphate cathode material using an iron-containing material as an iron source, which can replace iron phosphate as an iron source with low cost; and the prepared lithium iron phosphate cathode material has excellent electrochemical performance.
[0005] To achieve the above object, the present invention can adopt the following technical solutions:
[0006] On the one hand, the present invention provides a preparation method of a lithium iron phosphate cathode material, including: (1) acidifying an iron-containing waste, and filtering to obtain a filtrate; (2) adjusting the iron ion concentration in the filtrate to 10 g / L - 90 g / L to obtain an iron source solution; (3) mixing the iron source solution, a phosphorus source, a lithium source, and a carbon source, and dispersing to obtain a precursor; (4) spray-drying the precursor and sintering to obtain a lithium iron phosphate cathode material.
[0007] Preferably, in step (1) of the above preparation method, one or more of the following conditions are satisfied: (a) the particle size of the iron-containing waste is 30 um < D50 < 45 um; (b) the iron-containing waste contains iron red, and the content of iron red ≥ 66%; (c) the iron-containing waste contains one or more metals among Fe, Mn, Ni, K, Na, Mg, Cu, or Zn; (d) the iron-containing waste is selected from one or more of waste iron slag, pyrite cinder, or iron red waste; (e) the acidification of the iron-containing waste includes: adding the iron-containing waste to an excessive hydrochloric acid solution and stirring; wherein, the stirring speed is 800 revolutions per minute - 1000 revolutions per minute; and / or the stirring time is 2 h - 4 h.
[0008] Preferably, in step (2) of the above preparation method, the iron source solution satisfies one or more of the following conditions: (a) the iron ion concentration is 13 g / L; (b) the pH of the iron source solution is 1-2.5.
[0009] Preferably, in step (2) of the above preparation method, the pH value of the iron source solution is 1.
[0010] Preferably, in step (3) of the above preparation method, one or more of the following conditions are met: (a) the phosphorus source is selected from one or more of phosphoric acid, diammonium phosphate or diammonium hydrogen phosphate; (b) the lithium source is selected from one or more of lithium carbonate, lithium oxalate or lithium hydroxide; (c) the carbon source is selected from one or more of glucose, sucrose or starch; (d) the molar ratio of Fe in the iron source solution to P in the phosphorus source is 1:(1-1.2); (e) the molar ratio of Fe in the iron source solution to Li in the lithium source is 1:(1-1.05); (f) the molar ratio of Fe in the iron source solution to C in the carbon source is 1:(0.5-1.25).
[0011] Preferably, in step (4) of the above preparation method, the sintering satisfies one or more of the following conditions: (a) the sintering temperature is 500°C-1000°C; (b) the sintering is 2h-5h; (c) the dispersion is ball milling dispersion with a rotation speed of 2000 rpm-3000 rpm; (d) the dispersion is ball milling dispersion with a dispersion time of 2h-5h.
[0012] Another aspect of the present invention provides a lithium iron phosphate positive electrode material prepared by the preparation method of the present invention.
[0013] Another aspect of the present invention provides a positive electrode sheet, which includes the lithium iron phosphate positive electrode material of the present invention.
[0014] Another aspect of the present invention provides a battery, which includes the lithium iron phosphate positive electrode sheet of the present invention.
[0015] The beneficial effects of the present invention include at least:
[0016] (1) The method for preparing the lithium iron phosphate positive electrode material provided by the present invention uses iron-containing waste as raw material. After being treated by the method of the present invention, a lithium iron phosphate positive electrode material with high purity can still be prepared without other impurity removal and purification treatment; and the iron-containing waste as raw material replaces the expensive iron phosphate as the iron source for preparing the lithium iron phosphate positive electrode material, which not only realizes the utilization of waste materials but also greatly reduces the production cost. The raw material cost in the present invention is reduced by about 15% compared with the cost of iron phosphate as raw material; and the performance of the prepared lithium iron phosphate positive electrode material has no significant difference or is even better.
[0017] (3) The preparation method of the lithium iron phosphate positive electrode material provided by the present invention simplifies the process flow and improves production efficiency.
[0018] (4) The lithium iron phosphate positive electrode material prepared by the preparation method of the lithium iron phosphate positive electrode material provided by the present invention has excellent electrochemical performance, and the initial charge and discharge efficiency can reach 96.6%.
[0019] (5) The preparation method of the lithium iron phosphate positive electrode material provided by the present invention can control the phosphorus-iron ratio to solve the problem of poor performance consistency of lithium iron phosphate caused by the uncontrollable phosphorus-iron ratio in the prior art. DETAILED DESCRIPTION
[0020] The examples are provided to better illustrate the present invention, but the present invention is not limited to the examples. Therefore, those skilled in the art may make non-essential improvements and adjustments to the implementation scheme according to the above invention content, which still fall within the protection scope of the present invention.
[0021] The terms used herein are only used to describe specific embodiments and are not intended to limit the present disclosure. Unless the context has a significantly different meaning, expressions in the singular include expressions in the plural. As used herein, it should be understood that terms such as "include", "have", "include" are intended to indicate the presence of features, numbers, operations, materials, or combinations. The terms of the present invention are disclosed in the specification, and are not intended to exclude the possibility that one or more other features, numbers, operations, materials, or combinations thereof may exist or may be added. As used herein, " / " may be interpreted as "and" or "or", depending on the circumstances.
[0022] The embodiment of the present invention provides a method for preparing a lithium iron phosphate positive electrode material, comprising: (1) acidifying iron-containing waste and filtering to obtain a filtrate; (2) adjusting the iron ion concentration in the filtrate to 10 g / L-90 g / L to obtain an iron source solution; (3) mixing the iron source solution, a phosphorus source, a lithium source and a carbon source to disperse to obtain a precursor; (4) spray drying the precursor and sintering to obtain a lithium iron phosphate positive electrode material.
[0023] It should be noted that the iron source solution in the present invention is obtained by acidifying the iron-containing material, filtering, and adjusting the iron ion concentration of the filtrate to 10g / L-90g / L. The preparation method is simple and the conditions are mild. In addition, "iron-containing material" refers to waste containing red iron (ferric oxide), other than waste iron slag, pyrite cinder or red iron oxide waste. In addition, the method for adjusting the iron ion concentration includes but is not limited to adding deionized water to dilute the concentration.
[0024] It should also be noted that if the iron ion concentration in the present invention is too low or too high, there will be more impurities, and the electrochemical performance of the lithium iron phosphate cathode material prepared subsequently will be poor. In the present invention, the iron ion concentration can be 10 g / L - 90 g / L, such as 15 g / L - 85 g / L, 17 g / L - 87 g / L, 20 g / L - 80 g / L, 25 g / L - 70 g / L, 30 g / L - 50 g / L or 40 g / L - 55 g / L, etc.; or 20 g / L, 30 g / L, 40 g / L, 50 g / L, 60 g / L, 70 g / L or 80 g / L, etc.
[0025] It should also be noted that when using the iron-containing waste in the present invention as the raw material for preparing the lithium iron phosphate cathode material, after adding other raw materials, the impurity elements will not participate in the reaction to form by-products, and some impurity elements (such as Na element) will volatilize during sintering, and a high-purity lithium iron phosphate cathode material is prepared; in addition, the processes of dispersion, spray drying and sintering are all operation processes known in the art.
[0026] In some specific examples, in step (1) of the above preparation method, one or more of the following conditions are satisfied: (a) the particle size of the iron-containing waste is 30 μm < D50 < 45 μm; (b) the iron-containing waste contains iron oxide red, and the content of iron oxide red ≥ 66%; (c) the iron-containing waste contains one or more metals among Fe, Mn, Ni, K, Na, Mg, Cu or Zn; (d) the iron-containing waste is selected from one or more of iron slag, pyrite cinder or iron oxide red waste; (e) the acidification of the iron-containing waste includes: adding the iron-containing waste to an excessive amount of hydrochloric acid solution and stirring; wherein, the stirring speed is 800 revolutions per minute - 1000 revolutions per minute; and / or the stirring time is 2 h - 4 h.
[0027] It should be noted that when the iron-containing material in the present invention is acidified, the iron-containing material is first crushed into a material with a particle size of 30 μm < D50 < 45 μm, and the acidolysis rate is faster and the acidolysis is more complete. In addition, as described above, the iron-containing material contains iron oxide red, and preferably the content of iron oxide red ≥ 66%. In addition, the iron-containing material can also contain one or more metals among Fe, Mn, Ni, K, Na, Mg, Cu or Zn.
[0028] It should also be noted that the iron-containing waste contains iron oxide red. The higher the content of iron oxide red, the lower the impurity content of the lithium iron phosphate cathode material prepared. When the content of iron oxide red ≥ 66%, the impurity content of the lithium iron phosphate cathode material prepared meets the requirements in the present invention.
[0029] It should also be noted that the iron-containing material in the present invention can be selected from one or more of waste iron slag, pyrite cinder or red iron oxide waste. Specifically, waste iron slag comes from waste slag produced during the smelting process of steel mills, and its main components are Fe3O4, Fe2O3, etc., and also contains other elements such as C, S, Ni, Cu and their compounds; pyrite cinder is the cinder produced during the acid production process of pyrite, which contains a large amount of iron, mainly in the form of Fe2O3. In addition, it also contains SiO2, CaO, MgO, A12O3, etc.; red iron waste mainly comes from steel mills, and its main component is iron oxide, and also includes Ni, Mn, Zn, Cr, etc.; that is, through the present invention, the recycling and reuse of waste materials can be achieved, reducing environmental pollution.
[0030] It should also be noted that stirring can be performed during the acidification of the iron-containing material. The stirring method can be selected from methods known in the art, such as magnetic stirring or mechanical stirring, and the stirring speed can be 800 rpm-1000 rpm, such as 850 rpm, 900 rpm or 950 rpm, etc.; the stirring time can be 2h-4h. If the time is too short (<2h), the acidification is incomplete. If the acidification time is too long (>4h), the acidification rate and acidification degree do not change significantly. Therefore, 2h-4h can be selected in the present invention, such as 2.5h, 3h or 3.5h, etc.; more preferably, stirring at a speed of 800 rpm-1000 rpm for 2h-4h.
[0031] In some specific examples, in step (2) of the above preparation method, the iron source solution satisfies one or more of the following conditions: (a) the iron ion concentration is 13 g / L; (b) the pH of the iron source solution is 1-2.5.
[0032] It should be noted that in the present invention, the iron ion concentration is 13 g / L, and the electrochemical performance of the lithium iron phosphate positive electrode material prepared at this concentration is better; in addition, the pH of the iron source solution in the present invention also affects the electrochemical performance of the prepared lithium iron phosphate positive electrode material. If the pH is too high, there are more impurities and the electrochemical performance of the prepared lithium iron phosphate positive electrode material is poor; therefore, in the present invention, the pH of the iron source solution can be 1-2.5, such as 1.3, 1.5, 1.7, 1.9, 2.2 or 2.4, etc.
[0033] In some specific examples, in step (2) of the above preparation method, the pH value of the iron source solution is 1.
[0034] It should be noted that the pH of the iron source solution has an effect on the electrochemical performance of the prepared lithium iron phosphate cathode material. In the present invention, the preferred pH is 1, and the electrochemical performance of the lithium iron phosphate cathode material prepared at this pH is better. In addition, the present invention is more preferably an iron ion concentration of 13g / L and a pH of 1. At this time, the electrochemical performance of the lithium iron phosphate cathode material prepared by the iron source solution is better than other concentrations and pHs, and the first charge and discharge efficiency can reach 96.6%.
[0035] In some specific examples, in step (3) of the above preparation method, one or more of the following conditions are met: (a) the phosphorus source is selected from one or more of phosphoric acid, diammonium phosphate or diammonium hydrogen phosphate; (b) the lithium source is selected from one or more of lithium carbonate, lithium oxalate or lithium hydroxide; (c) the carbon source is selected from one or more of glucose, sucrose or starch; (d) the molar ratio of Fe in the iron source solution to P in the phosphorus source is 1:(1-1.2); (e) the molar ratio of Fe in the iron source solution to Li in the lithium source is 1:(1-1.05); (f) the molar ratio of Fe in the iron source solution to C in the carbon source is 1:(0.5-1.25).
[0036] It should be noted that the phosphorus source, lithium source and carbon source in the present invention are all known in the art, and the above-mentioned phosphoric acid, lithium source and carbon source are preferred; more preferably, the phosphorus source is diammonium phosphate, the lithium source is lithium carbonate, and the carbon source is glucose, and the electrochemical performance of the prepared lithium iron phosphate positive electrode material is more excellent.
[0037] It should also be noted that in the process of preparing lithium iron phosphate positive electrode materials, the molar ratio of Fe in the iron source solution to P in the phosphorus source, Li in the lithium source and C in the carbon source also has a certain influence on the electrochemical properties of the prepared lithium iron phosphate positive electrode materials. In the present invention, the molar ratio of Fe in the iron source solution to P in the phosphorus source can be 1:(1-1.2), such as 1:1.13, 1:1.15 or 1:1.17, etc.; in addition, the molar ratio of Fe in the iron source solution to Li in the lithium source can be 1:(1-1.05), such as 1:1.02, 1:03 or 1:1.05, etc.; in addition, the molar ratio of Fe in the iron source solution to C in the carbon source is 1:(0.5-1.25), such as 1:0.7, 1:0.9, 1:1.2 or 1.22, etc.: The electrochemical performance of the lithium iron phosphate positive electrode material prepared with the above ratios is better than that of other ratios.
[0038] In some specific examples, in step (4) of the above preparation method, sintering satisfies one or more of the following conditions: (a) sintering temperature is 500°C-1000°C; (b) sintering is 2h-5h; (c) dispersion is ball milling dispersion with a rotation speed of 2000 rpm-3000 rpm; (d) dispersion is ball milling dispersion with a dispersion time of 2h-5h.
[0039] It should be noted that the dispersion and sintering processes in the present invention are operating processes known in the art; for example, the sintering can be 500°C-1000°C (such as 600°C, 700°C or 800°C, etc.) and sintering for 2h-5h (such as 3h or 4h, etc.); the dispersion can be ball milling dispersion with a rotation speed of 2000 rpm-3000 rpm (such as 2300 rpm, 2500 rpm or 2800 rpm) and a time of 2h-5h (such as 3h or 4h, etc.).
[0040] The embodiment of the present invention also provides a lithium iron phosphate positive electrode material prepared by the preparation method of the present invention.
[0041] It should be noted that the lithium iron phosphate positive electrode material prepared by the preparation method of the present invention has excellent electrochemical properties, and the first charge and discharge efficiency can reach 96.6%.
[0042] An embodiment of the present invention further provides a positive electrode sheet, which includes the lithium iron phosphate positive electrode material of the present invention.
[0043] It should be noted that, as described above, the lithium iron phosphate positive electrode material in the present invention has excellent electrochemical properties, and can be prepared into a lithium iron phosphate positive electrode sheet by combining it with materials such as a conductive agent, a binder and a current collector (such as aluminum foil); in addition, the conductive agent, the binder and the current collector are all materials known in the art.
[0044] An embodiment of the present invention further provides a battery, which includes the lithium iron phosphate positive electrode sheet of the present invention.
[0045] It should be noted that, based on the excellent electrochemical properties of the lithium iron phosphate positive electrode material in the present invention, the lithium iron phosphate positive electrode sheet prepared therefrom can be assembled into a lithium iron phosphate battery; of course, it should be understood that the lithium iron phosphate battery also includes other components, such as an electrolyte, a negative electrode, a diaphragm or a battery shell, etc.; the electrolyte, the negative electrode, the diaphragm or the battery shell are all materials known in the art.
[0046] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with specific examples, but the content of the present invention is not limited to the following examples.
[0047] 1. Sample preparation
[0048] In the following examples, the iron red waste (iron-containing waste) used is from a steel plant, and its composition is shown in Table 1.
[0049] Table 1 Iron red waste components of examples and comparative examples
[0050]
[0051] Example 1
[0052] Preparation of iron source solution: add excess hydrochloric acid solution to iron red waste (the mass ratio of iron red waste to hydrochloric acid solution is 1:4, and the hydrochloric acid concentration is 20%), mechanically stir for 2 hours at a speed of 1000 rpm, and filter to obtain a filtrate and filter residue containing ferric chloride and other impurities; add 20% sodium hydroxide solution dropwise to the filtrate to neutralize excess hydrochloric acid, and then add water to adjust the pH value to 1 and the iron ion concentration to 13 g / L (when adjusting the iron ion concentration and pH value, the first step is to add deionized water to adjust the iron ion concentration to ensure that the iron ion concentration is within the required range, and then measure the pH value of the solution, and add sodium hydroxide solution / hydrochloric acid solution to adjust it. All operations for adjusting the concentration and pH value are carried out while stirring) to obtain an iron source solution.
[0053] Diammonium dihydrogen phosphate was added according to the molar ratio of Fe to P of 1:1.8, lithium carbonate was added according to the molar ratio of Fe to Li of 1:1.05, and glucose was added according to the molar ratio of Fe to C of 1:1. The mixture was ball milled for 2 h at a speed of 1000 rpm. The obtained slurry was spray dried and sintered at 700°C for 2 h in a mixed atmosphere of nitrogen and argon to obtain a lithium iron phosphate positive electrode material.
[0054] Example 2
[0055] Preparation of iron source solution: add excess hydrochloric acid solution to the iron red waste, mechanically stir for 2 hours at a speed of 1000 rpm, and filter to obtain a filtrate and filter residue containing ferric chloride and other impurities; add 20% sodium hydroxide solution dropwise to the filtrate to neutralize excess hydrochloric acid, and then add water to adjust the pH value to 1.6 and the iron ion concentration to 19 g / L to obtain an iron source solution.
[0056] Diammonium dihydrogen phosphate was added according to the molar ratio of Fe to P of 1:1.2, lithium carbonate was added according to the molar ratio of Fe to Li of 1:1.05, and glucose was added according to the molar ratio of Fe to C of 1:1.15. The mixture was ball-milled for 2 h at a speed of 1000 rpm. The obtained slurry was spray-dried (after spray drying, the particle size D50 = 0.45 ± 0.15 μm, D90 = 1.4 ± 0.55 μm) and sintered at 700 ° C for 2 h in a mixed atmosphere of nitrogen and argon to obtain a lithium iron phosphate positive electrode material.
[0057] Example 3
[0058] Preparation of iron source solution: add excess hydrochloric acid solution to the iron red waste, stir mechanically for 2 hours at a speed of 1000 rpm, and filter to obtain a filtrate and filter residue containing ferric chloride and other impurities; add 20% sodium hydroxide solution dropwise to the filtrate to neutralize excess hydrochloric acid, and then add water to adjust the pH value to 2 and the iron ion concentration to 26.8 g / L to obtain an iron source solution.
[0059] Diammonium dihydrogen phosphate was added according to the molar ratio of Fe to P of 1:1.16, lithium carbonate was added according to the molar ratio of Fe to Li of 1:1.05, and glucose was added according to the molar ratio of Fe to C of 1:1.1. The mixture was ball milled for 2 h at a speed of 1000 rpm. The obtained slurry was spray dried and sintered at 700°C for 2 h in a mixed atmosphere of nitrogen and argon to obtain a lithium iron phosphate positive electrode material.
[0060] Example 4
[0061] Preparation of iron source solution: add excess hydrochloric acid solution to the iron red waste, mechanically stir for 2 hours at a speed of 1000 rpm, and filter to obtain a filtrate and filter residue containing ferric chloride and other impurities; add 20% sodium hydroxide solution dropwise to the filtrate to neutralize excess hydrochloric acid, and then add water to adjust the pH value to 2 and the iron ion concentration to 45 g / L to obtain an iron source solution.
[0062] Diammonium dihydrogen phosphate was added according to the molar ratio of Fe to P of 1:1.16, lithium carbonate was added according to the molar ratio of Fe to Li of 1:1.05, and glucose was added according to the molar ratio of Fe to C of 1:1.1. The mixture was ball milled for 2 h at a speed of 1000 rpm. The obtained slurry was spray dried and sintered at 700°C for 2 h in a mixed atmosphere of nitrogen and argon to obtain a lithium iron phosphate positive electrode material.
[0063] Example 5
[0064] Preparation of iron source solution: add excess hydrochloric acid solution to the iron red waste, mechanically stir for 2 hours at a speed of 1000 rpm, and filter to obtain a filtrate and filter residue containing ferric chloride and other impurities; add 20% sodium hydroxide solution to the filtrate to neutralize excess hydrochloric acid, and then add water to adjust the pH value to 2 and the iron ion concentration to 60 g / L to obtain an iron source solution.
[0065] Diammonium dihydrogen phosphate was added according to the molar ratio of Fe to P of 1:1.16, lithium carbonate was added according to the molar ratio of Fe to Li of 1:1.05, and glucose was added according to the molar ratio of Fe to C of 1:1.1. The mixture was ball milled for 2 h at a speed of 1000 rpm. The obtained slurry was spray dried and sintered at 700°C for 2 h in a mixed atmosphere of nitrogen and argon to obtain a lithium iron phosphate positive electrode material.
[0066] Example 6
[0067] Preparation of iron source solution: add excess hydrochloric acid solution to the iron red waste, stir mechanically for 2 hours at a speed of 1000 rpm, and filter to obtain a filtrate and filter residue containing ferric chloride and other impurities; add 20% sodium hydroxide solution dropwise to the filtrate to neutralize excess hydrochloric acid, and then add water to adjust the pH value to 2 and the iron ion concentration to 90 g / L to obtain an iron source solution.
[0068] Diammonium dihydrogen phosphate was added according to the molar ratio of Fe to P of 1:1.16, lithium carbonate was added according to the molar ratio of Fe to Li of 1:1.05, and glucose was added according to the molar ratio of Fe to C of 1:1.1. The mixture was ball milled for 2 h at a speed of 1000 rpm. The obtained slurry was spray dried and sintered at 700°C for 2 h in a mixed atmosphere of nitrogen and argon to obtain a lithium iron phosphate positive electrode material.
[0069] Comparative Example 1
[0070] Preparation of iron source solution: add excess hydrochloric acid solution to the iron red waste, stir mechanically for 2 hours at a speed of 1000 rpm, and filter to obtain a filtrate and filter residue containing ferric chloride and other impurities; add 20% sodium hydroxide solution dropwise to the filtrate to neutralize excess hydrochloric acid, and then add water to adjust the pH>3, the iron ion concentration is 60g / L, and the iron source solution is obtained.
[0071] Diammonium dihydrogen phosphate was added at a molar ratio of Fe to P of 1:1.16, lithium carbonate was added at a molar ratio of Fe to Li of 1:1.05, and glucose was added at a molar ratio of Fe to C of 1:1.1. The mixture was ball milled for 2 h at a speed of 1000 rpm. The obtained slurry was spray dried and sintered at 700°C for 2 h in a mixed atmosphere of nitrogen and argon. However, lithium iron phosphate positive electrode material could not be obtained.
[0072] Comparative Example 2
[0073] Preparation of iron source solution: add excess hydrochloric acid solution to the iron red waste, stir mechanically for 2 hours at a speed of 1000 rpm, and filter to obtain a filtrate and filter residue containing ferric chloride and other impurities; add 20% sodium hydroxide solution dropwise to the filtrate to neutralize excess hydrochloric acid, and then add water to adjust the pH to <1, the iron ion concentration is 60 g / L, and an iron source solution is obtained.
[0074] Diammonium dihydrogen phosphate was added at a molar ratio of Fe to P of 1:1.16 (red flocs were formed after addition), lithium carbonate was added at a molar ratio of Fe to Li of 1:1.05, and glucose was added at a molar ratio of Fe to C of 1:1.1. The mixture was ball-milled for 2 h at a speed of 1000 rpm. The obtained slurry was spray-dried and sintered at 700°C for 2 h in a mixed atmosphere of nitrogen and argon. A second phase appeared after sintering, and pure lithium iron phosphate positive electrode material could not be obtained.
[0075] Comparative Example 3
[0076] Preparation of iron source solution: add excess hydrochloric acid solution to the iron red waste, mechanically stir for 2 hours at a speed of 1000 rpm, and filter to obtain a filtrate and filter residue containing ferric chloride and other impurities; add 20% sodium hydroxide solution dropwise to the filtrate to neutralize excess hydrochloric acid, and then add water to adjust the pH value to 2 and the iron ion concentration to 8 g / L to obtain an iron source solution.
[0077] Diammonium dihydrogen phosphate was added at a molar ratio of Fe to P of 1:1.16, lithium carbonate was added at a molar ratio of Fe to Li of 1:1.05, and glucose was added at a molar ratio of Fe to C of 1:1.1. The mixture was ball milled for 2 h at a speed of 1000 rpm. The obtained slurry was spray dried and sintered at 700°C for 2 h in a mixed atmosphere of nitrogen and argon. A second phase appeared after sintering, and the lithium iron phosphate positive electrode material could not be obtained.
[0078] Comparative Example 4
[0079] Preparation of iron source solution: add excess hydrochloric acid solution to the iron red waste, mechanically stir for 2 hours at a speed of 1000 rpm, and filter to obtain a filtrate and filter residue containing ferric chloride and other impurities; add 20% sodium hydroxide solution dropwise to the filtrate to neutralize excess hydrochloric acid, then add water to adjust the pH value to 2 and the iron ion concentration to 110 g / L to obtain an iron source solution.
[0080] Diammonium dihydrogen phosphate was added at a molar ratio of Fe to P of 1:1.16, lithium carbonate was added at a molar ratio of Fe to Li of 1:1.05, and glucose was added at a molar ratio of Fe to C of 1:1.1. The mixture was ball milled for 2 h at a speed of 1000 rpm. The obtained slurry was spray dried and sintered at 700°C for 2 h in a mixed atmosphere of nitrogen and argon. A second phase appeared after sintering, and the lithium iron phosphate positive electrode material could not be obtained.
[0081] 2. Sample testing
[0082] (I) Filtrate and iron source solution composition test
[0083] The ICP-OES test method (iron is selected at 259.94nm, manganese is selected at 257nm, nickel is selected at 231.604nm, potassium is selected at 766nm, sodium is selected at 589nm, magnesium is selected at 280 / 285nm, copper is selected at 324.7nm, zinc is selected at 206.2nm, and chromium is selected at 206.157nm) is used to test the composition of the filtrate filtered after acidification and the prepared iron source solution in Examples 1 to 6 and Comparative Examples 1 to 4, and the results are shown in Table 2 below.
[0084] Table 2 Compositions after acidification and pH adjustment in Examples 1 to 6 and Comparative Examples 1 to 3
[0085]
[0086]
[0087] From Table 2 above, we can know that:
[0088] As for the impurity Mn, in the iron source solution, the content of Examples 1 to 4 is significantly lower than that of Comparative Examples 1 to 4, and Examples 5 and 6 are not much different from Comparative Examples 1 to 3, but lower than Comparative Example 4;
[0089] As for the impurity Ni, in the iron source solution, the content of Examples 1 to 4 is significantly lower than that of Comparative Examples 1 to 4, and Examples 5 and 6 are not much different from Comparative Examples 1 to 3, but lower than Comparative Example 4;
[0090] As for impurity K, in the iron source solution, the content of Examples 1 to 4 is significantly lower than that of Comparative Examples 1 to 4, and Examples 5 and 6 are not much different from Comparative Examples 1 to 3, but lower than that of Comparative Example 4;
[0091] As for the impurity Na, in the iron source solution, the content of Examples 1 to 4 is significantly lower than that of Comparative Examples 1 to 4, and Examples 5 and 6 are not much different from Comparative Examples 1 to 3, but lower than that of Comparative Example 4;
[0092] As for the impurity Mg, in the iron source solution, the content of Examples 1 to 4 is significantly lower than that of Comparative Examples 1 to 4, and Examples 5 and 6 are not much different from Comparative Examples 1 to 3, but lower than Comparative Example 4;
[0093] As for the impurity Cu, in the iron source solution, the content of Examples 1 to 4 is significantly lower than that of Comparative Examples 1 to 4, and Examples 5 and 6 are not much different from Comparative Examples 1 to 3, but lower than that of Comparative Example 4;
[0094] As for the impurity Zn, in the iron source solution, the content of Examples 1 to 4 is significantly lower than that of Comparative Examples 1 to 4, and Examples 5 and 6 are not much different from Comparative Examples 1 to 3, but lower than Comparative Example 4;
[0095] As for the impurity Cr, in the iron source solution, the content of Examples 1 to 4 is significantly lower than that of Comparative Examples 1 to 4, and the content of Examples 5 and 6 is not much different from Comparative Examples 1 to 3, but lower than that of Comparative Example 4.
[0096] (II) Lithium iron phosphate cathode material composition test
[0097] The components of the lithium iron phosphate positive electrode materials prepared in Examples 1 to 6 and Comparative Examples 1 to 4 were tested, and the results are shown in Table 3 below.
[0098] Table 3 Lithium iron phosphate positive electrode material composition of Examples 1 to 6 and Comparative Examples 1 to 4
[0099]
[0100] Note: The iron content of the comparative example is higher than that of the example due to the following reasons: part of Fe reacts with other elements to produce the second phase during the reaction stage; part of Li does not participate in the reaction and exists in the form of free lithium. When the main content is detected, the influence of free lithium is excluded, so the overall Li content is low and the iron content is high.
[0101] It can be seen from Table 3 above that the prepared lithium iron phosphate positive electrode material:
[0102] As for the content of Li, Examples 1 to 6 are higher than Comparative Examples 2 to 4;
[0103] As for the content of Fe, Examples 1 to 6 are lower than Comparative Examples 2 to 4;
[0104] Regarding the content of P, Examples 1 to 6 are higher than Comparative Examples 2 to 4;
[0105] For the content of C, Examples 1 to 6 are higher than Comparative Examples 2 to 4;
[0106] As for the content of impurity Na, Examples 1 to 6 are lower than Comparative Examples 3 to 4;
[0107] For the content of impurity K, Examples 1 to 6 are significantly lower than Comparative Examples 2 to 4;
[0108] As for the content of impurity Ni, Examples 1 to 6 are significantly lower than Comparative Examples 2 to 4;
[0109] As for the content of impurity Mn, Examples 1 to 4 are lower than Comparative Examples 2 to 4, and Examples 5 to 6 are slightly higher than Comparative Examples 2 to 4;
[0110] As for the content of impurity Cr, Examples 1 to 6 are significantly lower than Comparative Examples 2 to 4;
[0111] As for the content of impurity Cu, Examples 1 to 6 are significantly lower than Comparative Examples 2 to 4;
[0112] As for the content of impurity Zn, Examples 1 to 6 are significantly lower than Comparative Examples 2 to 4;
[0113] As for the content of impurity Mg, Examples 1 to 6 are significantly lower than Comparative Examples 2 to 4;
[0114] In summary, it can be seen that the Li content of the lithium iron phosphate positive electrode material prepared based on the iron source solution in the present invention is higher than that of the comparative example, and the impurity content is basically lower than that of the comparative example, that is, the impurity content of the lithium iron phosphate positive electrode material prepared based on the iron source solution in the present invention is low.
[0115] (III) Electrochemical performance test of lithium iron phosphate cathode material
[0116] Button test method: Add lithium iron phosphate powder: SP: PVDF in a mass ratio of 90:5:5 into the degassing tank, degas and stir to form a uniform slurry, use a coater to evenly apply the slurry on aluminum foil, dry in a vacuum drying oven at 90°C for 16 hours, cut and assemble CR2016 button batteries in a glove box. To detect its electrochemical properties, the LiFePO4 / / Li system was subjected to constant current charge and discharge tests at room temperature using a blue battery test system, with a test voltage range of 2V-3.75V; the specific steps were: standing for 6 hours—constant current charging (0.1C) until the voltage reached 3.75V—constant voltage charging until the current reached 0.02C or the charging time exceeded half an hour—standing for 5 minutes—constant current discharge (0.1C) until the voltage reached 2V—standing for 5 minutes—constant current charging (1C) until the voltage reached 3.75V—constant voltage charging until the current reached 0.02C or the charging time exceeded half an hour—constant current discharge (1C) until the voltage reached 2V—standing for 5 minutes—end of test.
[0117] The composition of the lithium iron phosphate positive electrode materials prepared in Examples 1 to 6 and Comparative Examples 1 to 4 was tested using the button cell testing method. The results are shown in Table 3 below.
[0118] Table 4 Electrochemical properties of lithium iron phosphate positive electrode materials of Examples 1 to 6 and Comparative Examples 1 to 4
[0119]
[0120] It can be seen from Table 4 above that the 0.1C discharge of the lithium iron phosphate positive electrode materials prepared in Examples 1 to 6 is significantly higher than that of Comparative Examples 2 to 4, for example, the highest Example 4 (162.1 mAh / g) is about 27.6% higher than the lowest Comparative Example 4 (127 mAh / g); in addition, the 0.1C discharge of the lithium iron phosphate positive electrode materials prepared in Examples 1 to 6 is significantly higher than that of Comparative Examples 2 to 4, for example, Example 4 (153.8 mAh / g) is about 36.2% higher than that of Comparative Example 4 (112.9 mAh / g); in addition, the first efficiency of the lithium iron phosphate positive electrode materials prepared in Examples 1 to 6 is also much higher than that of Comparative Examples 2 to 4, for example, the highest Example 1 (96.6%) is 7.7% higher than the lowest Comparative Example 4 (88.9%). In summary, the lithium iron phosphate positive electrode material prepared in the present invention has good electrochemical properties.
[0121] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution of the present invention, which should be covered by the scope of the claims of the present invention.
Claims
1. A method for preparing a lithium iron phosphate positive electrode material, characterized in that: include: (1) acidifying the iron-containing waste and filtering to obtain a filtrate; (2) adjusting the iron ion concentration in the filtrate to 10 g / L-90 g / L to obtain an iron source solution; (3) mixing an iron source solution, a phosphorus source, a lithium source and a carbon source to disperse a precursor; (4) spray drying the precursor and sintering it to obtain a lithium iron phosphate positive electrode material.
2. The preparation method according to claim 1, characterized in that: In step (1), one or more of the following conditions are met: (a) The particle size of iron-containing waste is 30um <D50<45um; (b) The iron-containing waste contains red iron, and the content of red iron is ≥ 66%; (c) the iron-containing waste contains one or more metals selected from the group consisting of Fe, Mn, Ni, K, Na, Mg, Cu and Zn; (d) the iron-containing waste material is selected from one or more of waste iron slag, pyrite cinder or red iron oxide waste; (e) Acidification of iron-containing waste includes: adding the iron-containing waste to an excess amount of hydrochloric acid solution and stirring; wherein the stirring speed is 800 rpm to 1000 rpm; and / or the stirring time is 2h to 4h.
3. The preparation method according to claim 1 or 2, characterized in that: In step (2), the iron source solution satisfies one or more of the following conditions: (a) Iron ion concentration is 13 g / L; (b) The pH of the iron source solution is 1-2.
5.
4. The preparation method according to claim 3, characterized in that: The pH of the iron source solution was 1.
5. The preparation method according to claim 3, characterized in that: In step (3), one or more of the following conditions are met: (a) the phosphorus source is selected from one or more of phosphoric acid, diammonium phosphate or diammonium hydrogen phosphate; (b) the lithium source is selected from one or more of lithium carbonate, lithium oxalate or lithium hydroxide; (c) the carbon source is selected from one or more of glucose, sucrose or starch; (d) the molar ratio of Fe in the iron source solution to P in the phosphorus source is 1:(1-1.2); (e) The molar ratio of Fe in the iron source solution to Li in the lithium source is 1:(1-1.05); (f) The molar ratio of Fe in the iron source solution to C in the carbon source is 1:(0.5-1.25).
6. The preparation method according to claim 1, 2 or 4, characterized in that: In step (3), one or more of the following conditions are met: (a) the phosphorus source is selected from one or more of phosphoric acid, diammonium phosphate or diammonium hydrogen phosphate; (b) the lithium source is selected from one or more of lithium carbonate, lithium oxalate or lithium hydroxide; (c) the carbon source is selected from one or more of glucose, sucrose or starch; (d) the molar ratio of Fe in the iron source solution to P in the phosphorus source is 1:(1-1.2); (e) the molar ratio of Fe in the iron source solution to Li in the lithium source is 1:(1-1.05); (f) The molar ratio of Fe in the iron source solution to C in the carbon source is 1:(0.5-1.25).
7. The preparation method according to claim 1, 2, 4 or 5, characterized in that: In step (4), one or more of the following conditions are met: (a) The sintering temperature is 500°C-1000°C; (b) sintering for 2h-5h; (c) dispersing by ball milling at a rotation speed of 2000 rpm to 3000 rpm; (d) Dispersion is performed by ball milling, and the dispersion time is 2h-5h.
8. A lithium iron phosphate positive electrode material prepared by the preparation method according to any one of claims 1 to 7.
9. A positive electrode sheet, characterized in that: Including the lithium iron phosphate positive electrode material as described in claim 8.
10. A battery, characterized in that Including the lithium iron phosphate positive electrode sheet as described in claim 9.
